Prolyl Hydroxylase Domain-2 Silencing Induced by Hydrodynamic Limb Vein Injection Enhances Vascular Regeneration in Critical Limb Ischemia Mice through Activation of Multiple Genes - Wu, Shourong; Zhang, Jing; Huang, Can; Jia, Huizhen; Wang, Yunxia; Xu, Zhiling; Yang, Li; Miyagishi, Makoto; Kasim, Vivi (Current Gene Therapy, 2015)
Therapeutic revascularization had been considered as the most potential strategy for treating ischemic diseases. Reconstruction of mature blood vessels, which is the key for functional revascularization, is a complex process involving multiple angiogenesis factors. Attempts had been made to promote functional revascularization by delivering vectors or other macromolecules that could positively regulate angiogenesis; however, the delivery method of these therapeutic angiogenesis factors had been mostly limited to direct intramuscular injection. In this study, we showed that compared to intramuscular injection, the hydrodynamic limb vein (HLV) injection of naked shorthairpin RNA expression plasmid targeting PHD2 (shPHD2) into critical himblimb ischemia mice could increase not only the expressions of HIF-dependent and HIF-independent angiogenic factors, but also tissue protective factors involved in various endogenous pathways more efficiently. We also found that PHD2-silencing enhanced innate endogenous recovery mechanism, as the expression levels of these factors had been slightly upregulated merely by the ischemic condition. Finally, we showed that HLV injection of shPHD2 promoted the formation of mature and functional vessels, and thus, enhances the recovery of ischemic hindlimbs more efficiently. These results suggest that HLV delivery of shPHD2 might become a promising treatment strategy to promote vascular regeneration in critical limb ischemia disease via enhancing innate endogenous pathways.
Keywords: PHD2